2012
DOI: 10.1167/iovs.11-8453
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Overnight Orthokeratology on Axial Length Elongation in Childhood Myopia: A 5-Year Follow-Up Study

Abstract: The current 5-year follow-up study indicated that OK can suppress axial length elongation in childhood myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
302
2
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(340 citation statements)
references
References 48 publications
(57 reference statements)
21
302
2
15
Order By: Relevance
“…These optical strategies appear to slow the progression of myopia by B30-55% and without adverse effects. [38][39][40][41][42] It has been suggested that reducing the progression of myopia by as little as 33% would reduce the number of highly myopic eyes (4 À 5.00 D) by as many as 75%. 43 Data from a longer term clinical study, involving the use of contact lenses to reduce the hyperopic defocus at the peripheral retina, showed that the ability of these lenses to slow the progression of myopia was a consistent 40% per year over the study period of 43 months.…”
Section: Optical Interventionmentioning
confidence: 99%
“…These optical strategies appear to slow the progression of myopia by B30-55% and without adverse effects. [38][39][40][41][42] It has been suggested that reducing the progression of myopia by as little as 33% would reduce the number of highly myopic eyes (4 À 5.00 D) by as many as 75%. 43 Data from a longer term clinical study, involving the use of contact lenses to reduce the hyperopic defocus at the peripheral retina, showed that the ability of these lenses to slow the progression of myopia was a consistent 40% per year over the study period of 43 months.…”
Section: Optical Interventionmentioning
confidence: 99%
“…Ortho-K is the application of specially-designed, reverse-geometry; rigid-gas-permeable contact lenses worn only while sleeping to temporarily reshape the cornea, such that refractive error is corrected without the need to wear any correction during waking hours. To date, numerous clinical studies have reported a beneficial effect of Ortho-K on slowing or stopping myopic progression [20][21][22][23][24][25]. Ortho-K requires adherence to prescribed wear time, and children in one retrospective study were shown to be very adherent to the prescribed Ortho-K wearing schedule [26].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the age range being different, both studies showed similar retention patterns. Furthermore, the Japanese study followed the subjects for five years, and the regulation effect, despite lower, continued over this period [33].…”
Section: Discussionmentioning
confidence: 99%